Effective Methods In Teaching Mathematics - Tufliyev Egamberdi Olimovich; Bozarov Dilmurod Uralovich; Muhammadiyev Jahongir Matlubovich (International Journal on Orange Technologies, 2021)
The article talks about the importance of mathematics, the reforms implemented and being implemented in our country for the development of this science, as well as the contribution of oriental scientists to the science of mathematics and its development. At the same time, important aspects of the methods used in teaching science have been highlighted